KUALITAS PELAYANAN, PRODUK DAN PROMOSI SEBAGAI VARIABEL INTERVENING UNTUK MELIHAT LOYALITAS KONSUMEN PENIKMAT COFFEE DI KOTA BUKITTINGGI - Andria Ningsih; Eka Hendrayani; Mike Triani; Mustika Lukman Arief (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2022)
Changes in consumer desires today have a lot of positive impacts on entrepreneurs, especially coffee shops. Sometimes people prefer to come just to enjoy just a drink according to the menu provided at the cafe. This study aims to determine the effect of service quality, product effect on promotion, whether the effect of service and product quality has a direct effect on consumer loyalty and service and product quality affect consumer loyalty through promotion. The population is consumers who often come to the cafe. Sampling using the technique of accidental sampling, the number of respondents as many as 100. The method of data collection using observation, and questionnaires, descriptive data analysis techniques, classical assumption test and path. The findings obtained are the quality of service and product quality have an effect on promotion, service quality has a direct effect on consumer loyalty, while the product has no effect on consumer loyalty through promotion. Although consumers do not pay attention to the quality of the products offered, the quality of taste should be maintained, so that new and old customers continue to come to visit the KOPIGO Bukittinggi cafe